Removal of Scale from Feed-water in Thermal Power Plant by Magnetic Separation -Analysis of Oxygenated Treatment Scale-. (September 2019) - Hiramatsu, M; Yamamoto, J; Akiyama, Y; Mishima, F; Nishijima, S; Okada, H; Hirota, N; Yamaji, T; Matsuura, H; Namba, S; Sekine, T; Kobayashi, Y; et al.
Abstract: One of the reasons of the deterioration of the power generation efficiency of the thermal power generation is the adhesion of the iron scale generated by the corrosion of the pipe to the inner wall of the feed-water system. Focusing on the magnetic property of scale, we studied on the removal of scales in the feed-water system by high gradient magnetic separation (HGMS) using the superconducting magnet. In this study, we targeted the thermal power plants adopting oxygenated treatment (OT). In order to determine the installation site and the magnetic separation condition of the HGMS system, we analyzed the OT scale and then clarified the aggregation/composite states by magnetic separation experiment. It is concluded that low-pressure feed-water heater drain is suitable for installation site of HGMS system. In addition, it was clarified that homogeneous aggregation particles existed in the OT scale.